2021
DOI: 10.1002/adfm.202103062
|View full text |Cite
|
Sign up to set email alerts
|

Universal Platform for Scalable Semiconductor‐Superconductor Nanowire Networks

Abstract: Semiconductor-superconductor hybrids are commonly used in research on topological quantum computation. Traditionally, top-down approaches involving dry or wet etching are used to define the device geometry. These often aggressive processes risk causing damage to material surfaces, giving rise to scattering sites particularly problematic for quantum applications. Here, a method that maintains the flexibility and scalability of selective area grown nanowire networks while omitting the necessity of etching to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The use of nanowalls as shadowing objects, however, has been mainly developed for the device chip (Figure h–j). In particular, the nanowire is transferred or grown in-plane next to a wall on the device chip prior to the shadow deposition, such that after the superconductor deposition the device is complete and no further fabrication steps are required ,, . The elimination of fabrication steps in hybrid devices using transferred VLS nanowires in combination with shadow-wall deposition have yielded significant improvements in transport properties, device quality, and reproducibility , .…”
Section: Iii–v Nanowiresmentioning
confidence: 99%
“…The use of nanowalls as shadowing objects, however, has been mainly developed for the device chip (Figure h–j). In particular, the nanowire is transferred or grown in-plane next to a wall on the device chip prior to the shadow deposition, such that after the superconductor deposition the device is complete and no further fabrication steps are required ,, . The elimination of fabrication steps in hybrid devices using transferred VLS nanowires in combination with shadow-wall deposition have yielded significant improvements in transport properties, device quality, and reproducibility , .…”
Section: Iii–v Nanowiresmentioning
confidence: 99%
“…Selective area epitaxy (SAE) is one of the most important methods for in-plane nanowires and nanowire networks growth because it enables the density, position, diameter and pattern of openings to be well controlled to produce various in-plane nanostructure arrays [16][17][18][19][20]. To date, SAE has been used in different epitaxial growth-techniques such as metal organic chemical vapor deposition, chemical beam epitaxy and molecular-beam epitaxy (MBE) [21][22][23]. Among them, MBE-SAE technique has unique advantages due to its ultrahigh source purity, ultra-high vacuum growth condition and low growth temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Josephson junctions enable many applications by developing semiconductorsuperconductor hybrid structures. Moreover, recent progress in quantum computing, quantum sensing, and cryogenic electronics has shown that semiconductor-superconductor hybrid structures are needed for artificial intelligence, enhanced sensor performance, next-generation computing, signal processing, and quantum optoelectronic devices [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%